Vibration suppression of multistorey building using adaptive tuned mass damper - Mardzuki, Muhammad Imran; Md Nor, Khairul Affendy; Nordin, Nor Hidayati Diyana (Persatuan Saintis Muslim Malaysia (PERINTIS), 2024)
An efficient engineering innovation called a vibration absorber is frequently employed to lessen vibration brought by unanticipated conditions like seismic stimulation or other external forces acting on the structure. By adjusting the absorber's mass and stiffness parameters to match the structure's natural frequency, a traditional vibration absorber can lessen the vibration of the structure. Conventional vibration absorbers, however, have a set of natural frequency that cannot be altered. To address this problem, an adaptive vibration absorber was created in this study. When a variable excitation force is applied, an adaptive vibration absorber may modify its stiffness to tune its natural frequency, enabling it to overcome the off-tuning state and resonate with the natural frequency of the main structure. This can be done by manipulating the length of spring of the absorber. The natural frequency of a three-story building construction was measured experimentally. Based on the results, a vibration absorber with a resonance frequency of 3 Hz was developed, resulting in a vibration reduction of more than 50%. To further evaluate the adaptive vibration absorber's effectiveness, it was modified to resonate at 4 Hz when installed on the three-story structure. The vibration reduction was greater than 30% at this customized resonance frequency.